Students purchase intention towards counterfeit luxury fashion products / Nur Faziana Saadon - Saadon, Nur Faziana (2015)
This research was conducted to carry out a study entitled “Students Purchase Intentions Towards Counterfeit Luxury Fashion Products”. The purpose of this study is to investigate the key factors which lead to the purchase intentions among undergraduates. The four independent variables are information susceptibility, normative susceptibility, price consciousness and novelty seeking. The sample size used for this study was 168 respondents. Data was obtained by using simple random sampling. The study seeks to identify the most important factors that influence purchase intentions of counterfeit luxury fashion products among students, to examine the relationship between independent variables (information susceptibility, normative susceptibility, price consciousness and novelty seeking) and dependent variable (student purchase intentions) Finding shows that, only one out of four independent variable (price consciousness) that have negative relationship with dependent variable (students purchase intentions), others independent variables (information susceptibility, normative susceptibility and novelty seeking) show significant and positive relationship with the dependent variable (students purchase intentions). The most significant predictor variable on purchase intentions of counterfeit luxury fashion products among students is information susceptibility at 0.757 (75.7%). Overall, researchers achieved to answer all objectives in the study.